Effect of Extraction Methods on the Antibacterial Activity of Spices (garlic, cinnamon, turmeric, clove) against Escherichia coli K12 (JM109) - Abdullah, Talal; Albeshari, Kahlan; Ahmed, Idris Adewale; Baharuddin, Aida (Asian Journal of Biological and Life Sciences, 2017)
In this study, simple extraction methods were used to determine the antibacterial activity of crude extracts of garlic, cloves, cinnamon and turmeric against Escherichia coli K12 (JM109). These extraction methods include ethanolic extraction, aqueous extraction, soaking, boiling and juicing. These methods were applied to spices in different forms, for example the soaking method was used for crushed spices while the boiling method was employed for whole, crushed and powdered forms. The disc diffusion method was utilised to determine antibacterial activity. In the case of garlic, the results revealed that soaking for 3 hours in a sterile aqueous solution (using the crushed form), boiling (using crushed and powdered forms) and using juice extraction caused antibacterial activity to occur against E. coli K12 (JM109). Fifteen grams of crushed garlic soaked in 20 ml of sterile aqueous solution exhibited the best inhibition zone of 19.6 ± 0.64 mm. Cloves extract acquired from using ethanolic extraction, aqueous extraction, soaking and boiling extraction methods displayed antibacterial activity against E. coli K12 (JM109). In the case of the soaking method, these results were obtained when crushed cloves were soaked for 3 hours. While in the case of the boiling method, both crushed and powdered cloves were used. The ethanolic extract of cloves at 0.40 g/ml produced an inhibition zone of 10.0 ± 1.0 mm, while the aqueous extract produced an inhibition zone of 13.3 ± 0.58 at 0.72 g/ml. The antibacterial activities from crude extracts of cinnamon and turmeric were not detected against E. coli K12 (JM109).
Keywords: Antibacterial activities; Crude extract; E. coli K12 (JM109); Medicinal spices